1996
DOI: 10.1177/01461672962212008
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effects of Blame Attributions on Feelings of Anger

Abstract: Two structural equation models are presented to examine the relationship between anger and blame. In the first model, attributions of blame mediate the relationship between feelings of anger and attributions concerning the provoker's intentions to harm, his or her justification in harming, and the amount of harm done. In the second model, anger and blame exist in a reciprocal relationship. The self-reports of 158 individuals concerning an incident in which they had been harmed were analyzed using LISREL VIII. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
114
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(120 citation statements)
references
References 38 publications
6
114
0
Order By: Relevance
“…For example, studies by Young and Saxe (2011) found that judgments of purity violations (e.g., incest) were less susceptible to manipulations of intentionality than judgments of harm (e.g., an act of incest was still wrong even if the actors did not know it was incest). Though very important, intentionality is only one factor among a number of factors that influence judgments of wrongdoing and blame (Monroe, Guglielmo, & Malle, 2012;Quigley & Tedeschi, 1996). The present findings suggest that factors related to consent, cultural norms, romantic love, coercion, and even the symbolic meaning of the act (e.g., whether the actors were performing theatrically) were all recognized by a number of participants as influential in their judgments of purity violations.…”
Section: Running Head: Moral Emotions and Mitigating Circumstances 20mentioning
confidence: 57%
See 3 more Smart Citations
“…For example, studies by Young and Saxe (2011) found that judgments of purity violations (e.g., incest) were less susceptible to manipulations of intentionality than judgments of harm (e.g., an act of incest was still wrong even if the actors did not know it was incest). Though very important, intentionality is only one factor among a number of factors that influence judgments of wrongdoing and blame (Monroe, Guglielmo, & Malle, 2012;Quigley & Tedeschi, 1996). The present findings suggest that factors related to consent, cultural norms, romantic love, coercion, and even the symbolic meaning of the act (e.g., whether the actors were performing theatrically) were all recognized by a number of participants as influential in their judgments of purity violations.…”
Section: Running Head: Moral Emotions and Mitigating Circumstances 20mentioning
confidence: 57%
“…Anger has long been understood as an emotional response to perceived wrongdoing, particularly intentional and unjustified harm, or acts of injustice, including violations of a person's rights (Averill, 1982;Batson, Chao, & Givens, 2009;Goldberg, Lerner, & Tetlock, 1999;Quigley & Tedeschi, 1996;Rozin et al, 1999). Although there is some disagreement about the exact relationship between anger and judgments of wrongdoing or blame (i.e., whether anger precedes, co-occurs with, or follows from these judgments; see e.g., Averill, 1982;Quigley & Tedeschi, 1996;Weiner, 1995), the relationship is nonetheless robust, such that changes in moral judgment tend to reflect corresponding changes in anger, and vice versa (see pilot study discussed below).…”
Section: Anger Disgust and Moral Judgmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has show that perceived intentional harm evokes anger (Bentacourt & Blair, 1992) as well as blame (e.g., Shaver, 1985), and that these two emotions interact with one-another. Anger, like sympathy, is a moral emotion, Identifiability and punitiveness 6 which can produce strong inferences of blame (Averill, 1983;Weiner, 1995); Blame, likewise, intensifies anger, such that anger and blame have a significant recursive relationship (Quigley, & Tedeschi, 1996). Moreover, reactions of anger and blame naturally induce a desire to punish (Lerner, Goldberg, & Tetlock, 1998;Solomon, 1990).…”
Section: Adam Smith the Theory Of Moral Sentimentsmentioning
confidence: 99%